소나무 집성판의 표면화장 재료별 외관품질 및 접착성 평가 - 소원택; Won Tek So (목재공학, 2007)
This experiment was carried out to investigate the appearance and surface gluing characteristics of laminated boards overlaied with teak sliced veneer, printing paper, wall paper, cotton cloth, and wool cloth, The overlaying sheets were glued on the laminated boards with polyvinyl acetate emulsion adhesives and the species for laminated boards was red pine. The obtained results are summarized as follows; in case of the teak sliced veneer overlaied boards, the appearance quality was very good and showed the first grade of KS standard. but the delamination rate was 44.0% and 895% for cold water or warm water dipping treatments, respectively, so the wet gluing properties were very bed. In the case of the paper or cloth overlaied boards, the appearance quality was same good and showed the first grade of KS standard, but their delamination rate was 10~20% and 39.3~49.0 for cold water or warm water dipping treatments, respectively, so the wet gluing properties were bed, relatively better than sliced veneer overlaied boards. The present work showed that appearance of laminated boards overlaid with several sheets appeared quite positive in terms of secondary gluing qualities of laminated boards, suggesting that sliced veneer, paper, and cloth would be appropriate for the overlaying materials of laminated boards. 적절한 화장재료를 표면에 오버레이하는 방법으로 집성판을 2차가공하여 부가가치를 높이려는 목적으로 국산 소나무 소경 간벌목을 제재하여 집성판을 제조하고 표면화장 재료로서 화장단판, 종이류, 포류를 집성판의 표면에 오버레이 접착가공을 설시하였다. 제조된 화장집성판의 외관품질과 접착성을 조사하고 국산재의 집성이용 및 화장효과에 대한 성능을 평가한 결과를 요약하면 다음과 같다. 티크 슬라이스드 단판 오버레이 화장집성판의 경우 미약한 단판 부풀음, 균열 및 접합틈새가 발생하였고 종이 및 직물류 오버레이 화장집성판의 경우 미약한 밀림현상이 발생하였으나 전체적으로 재면 및 겉모양 품질은 양호하였으며 KS규격의 1급에 해당하였다. 화장집성판의 박리율을 비교했을 때 단판이 종이 빛 직물류 오버레이보다 내수접착성이 불량하였다.